Proceedings of the 4(th) BEAT-PCD Conference and 5(th) PCD Training School - Gardner, Laura E. (BMC Proc, 2020)
Primary ciliary dyskinesia (PCD) is an inherited ciliopathy leading to chronic suppurative lung disease, chronic rhinosinusitis, middle ear disease, sub-fertility and situs abnormalities. As PCD is rare, it is important that scientists and clinicians foster international collaborations to share expertise in order to provide the best possible diagnostic and management strategies. ‘Better Experimental Approaches to Treat Primary Ciliary Dyskinesia’ (BEAT-PCD) is a multidisciplinary network funded by EU COST Action (BM1407) to coordinate innovative basic science and clinical research from across the world to drive advances in the field. The fourth and final BEAT-PCD Conference and fifth PCD Training School were held jointly in March 2019 in Poznan, Poland. The varied program of plenaries, workshops, break-out sessions, oral and poster presentations were aimed to enhance the knowledge and skills of delegates, whilst also providing a collaborative platform to exchange ideas. In this final BEAT-PCD conference we were able to build upon programmes developed throughout the lifetime of the COST Action. These proceedings report on the conference, highlighting some of the successes of the BEAT-PCD programme.